2006
DOI: 10.1148/radiol.2411051075
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Fibroids: Contrast-enhanced MR Angiography to Predict Ovarian Artery Supply—Initial Experience

Abstract: Contrast-enhanced MR angiography can help predict ovarian artery supply of uterine fibroids.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(16 citation statements)
references
References 23 publications
1
14
0
1
Order By: Relevance
“…Moreover, longer magnet times theoretically increase the risk of acoustic and thermal injury to the fetus [18]. It is also unlikely that this complex vascular anatomy would be better visualized with intravenous MR contrast agents such as gadolinium, which are not recommended for use during pregnancy [18,19]. More promisingly, future research in this area could employ balanced fast field echo/true fast imaging with steady-state precession imaging to overcome the technical challenge of variations in uteropelvic blood flow.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, longer magnet times theoretically increase the risk of acoustic and thermal injury to the fetus [18]. It is also unlikely that this complex vascular anatomy would be better visualized with intravenous MR contrast agents such as gadolinium, which are not recommended for use during pregnancy [18,19]. More promisingly, future research in this area could employ balanced fast field echo/true fast imaging with steady-state precession imaging to overcome the technical challenge of variations in uteropelvic blood flow.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Binkert et al reported a relevantly altered procedure due to ovarian artery supply in only 6 % of cases [31]. Alternatively, significant collaterals can be reliably detected and classified by preinterventional MRA [32]. Reducing the overall number of angiographic images acquired during UAE by use of lower frame rates is another important measure.…”
Section: Digital Subtraction Angiographymentioning
confidence: 99%
“…Hierdurch kann während der Intervention die Strahlenexposition sowohl für die Patientin als auch für die Interventionalisten reduziert werden [18]. Die MRA kann darüber hinaus eine relevante Versorgung des Myoms durch die A. ovarica ausschließen, ein nicht selektives Angiogramm ist dann verzichtbar [9].…”
Section: » Zur Dokumentation Undunclassified